Multiple kinetic processes of lamellar growth in crystallization of stretched lightly crosslinked polyethylene. (16th January 2023) - Song, Kun; Liu, Dong; Wu, Lin-Feng; Wang, Zhe
Abstract: The growth of polymer crystals is accompanied by the change of interior conditions as time evolves. Therefore, its underlying mechanism should be time-dependent. Here, we investigate the process of lamellar growth by measuring stretched lightly crosslinked high-density polyethylene samples with in situ small-angle X-ray scattering and wide-angle X-ray diffraction. Two analysis methods are used to track the lamellar radius. It is found that the lamellar growth sequentially undergoes three stages, i.e., the interface-controlled stage, the diffusion-controlled stage, and the crystal perfection stage through Ostwald ripening mechanism. The transition between the first and the second stages is related to the competition between the diffusion of chains towards the growth surface and the consumption of chains at the surface in the ideal interfacial kinetics. This transition is significantly affected by the yielding of the sample. The second transition corresponds to the depletion of crystallizable chains, and is directly reflected by the decrease of the polydispersity of lamella radius. These results highlight the importance of the chain consumption in determining the mechanism of lamellar growth. Graphical abstract: Image 1 Highlights: An approach for rapidly tracking lamellar growth in FIC by integrating SAXS intensity. Lamellar growth is found to sequentially undergo three kinetic stages. Chain diffusion and consumption play the key role in determining lamella growth mode.